High sensitive C reactive protein as an inflammatory indicator in preeclampsia - Sayyed, Anjum A. K.; Pratinidhi, Shilpa A. (International Journal of Research in Medical Sciences, 2020)
Background: Preeclampsia is one of the most serious complications of pregnancy and one of the leading cause of maternal, prenatal morbidity and mortality. The present study was carried out to estimate serum high sensitive C- reactive protein in both mild and severe preeclampsia as an indicator of inflammation and to correlate Hs-CRP with blood pressure. Methods: A case control study was conducted in the Department of Biochemistry and Department of Obstetrics and Gynecology, MIMER Medical College and Bhausaheb Sardesai Rural Hospital Talegaon Dabhade, Pune. The study group include 50 cases of normal pregnant women, 43 clinically diagnosed cases of mild preeclampsia and 7 cases of severe preeclampsia in second and third trimester of pregnancy. 2 ml venous blood samples was collected from all the study participants for estimation of Hs-CRP by ultra-sensitive immunoturbidometric assay spin react method. Results: There was signiﬁcant increase in the mean serum Hs-CRP levels in normal pregnant women and mild preeclamptic women (p<0.001). Serum Hs-CRP levels were signiﬁcantly higher in severe preeclamspia than mild preeclamptic women (p<0.001). The degree of inflammation increases as HsCRP rises. Hence, present study shows that HsCRP levels increases as disease progresses from mild to severe condition. Significant positive correlations was found between Hs-CRP and Blood Pressure in preeclampsia. Conclusions: In preeclampsia there is an exaggeration of systemic inflammatory response that might induce reactive oxygen species which further induces endothelial dysfunction. This leads to clinical symptoms of hypertension and proteinuria in preeclampsia. Early detection might minimise systemic complications and maternal death due to preeclampsia. Hence, HsCRP may be used as an important indicator of severity of preeclampsia.